2014
DOI: 10.5664/jcsm.3858
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Complaints in Older Blacks: Do Demographic and Health Indices Explain Poor Sleep Quality and Duration?

Abstract: Objective: To examine the relationship between measures of sleep quality and the presence of commonly encountered comorbid and sociodemographic conditions in elderly Black subjects. Method: Analyses included participants from the Baltimore Study of Black Aging (BSBA; n = 450; mean age 71.43 years; SD 9.21). Pittsburgh Sleep Quality Index (PSQI) measured overall sleep pattern and quality. Self-reported and objective measures of physical and mental health data and demographic information were collected for all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
4
7
2
Order By: Relevance
“…We found that participants who dropped out of the study did not significantly differ by sex, education, depressive symptoms, or perceived stress level from those who completed both waves. These findings were similar to what other studies have reported ( Aiken-Morgan et al, 2015 ; Gamaldo et al, 2014 ). However, there were significant differences between completers and dropouts by age categories (Pearson χ 2 (3) = 20.33, p = .000) and family income ( t (576) = −2.09, p = .037), such that those who remained in the study were older and had higher monthly incomes versus those who dropped out.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…We found that participants who dropped out of the study did not significantly differ by sex, education, depressive symptoms, or perceived stress level from those who completed both waves. These findings were similar to what other studies have reported ( Aiken-Morgan et al, 2015 ; Gamaldo et al, 2014 ). However, there were significant differences between completers and dropouts by age categories (Pearson χ 2 (3) = 20.33, p = .000) and family income ( t (576) = −2.09, p = .037), such that those who remained in the study were older and had higher monthly incomes versus those who dropped out.…”
Section: Methodssupporting
confidence: 93%
“…Each testing session lasted approximately 2.5 h and consisted of a face-to-face interview in which participants completed a battery of cognitive tests, three blood pressure and lung functioning measurements, as well as measures that assessed demographic and other health-related factors. Data collection lasted 18 months and took place between 2006 and 2008 ( Aiken-Morgan, Gamaldo, Sims, Allaire, & Whitfield, 2015 ; Gamaldo et al, 2014 ; Sims et al, 2015 ; Thorpe, Clay, Szanton, Allaire, & Whitfield, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased sleep duration has been shown to be associated with increased morbidity and mortality [ 1 3 ]. Research suggests that factors such as socio-demographic and comorbid health factors [ 4 ], psychosocial stress [ 5 ], and lifestyle [ 6 ] are associated with sleep quality and duration. Hence, sleep duration and quality are not only medicine issue but also a socio-demographic issue.…”
Section: Introductionmentioning
confidence: 99%
“…However this finding was in agreement with previous work. 58,59 While there are some data suggesting that African American women are more likely to report poorer sleep quality than African American men, 28 other studies have observed no significant gender differences among African Americans for sleep quality and/ or sleep duration. 58,59 In the current study, African American women were significantly older and reported more chronic conditions than African American men.…”
Section: Discussionmentioning
confidence: 99%